2014
DOI: 10.5888/pcd11.140189
|View full text |Cite
|
Sign up to set email alerts
|

Rural–Urban Differences in Objective and Subjective Measures of Physical Activity: Findings From the National Health and Nutrition Examination Survey (NHANES) 2003–2006

Abstract: IntroductionLower levels of physical activity among rural relative to urban residents have been suggested as an important contributor to rural–urban health disparity; however, empirical evidence is sparse.MethodsWe examined rural–urban differences in 4 objective physical activity measures (2 intensity thresholds by 2 bout lengths) and 4 subjective measures (total, leisure, household, and transportation) in a nationally representative sample of participants in the National Health and Nutrition Examination Surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
103
1
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 114 publications
(111 citation statements)
references
References 16 publications
5
103
1
2
Order By: Relevance
“…The items used to measure aerobic PA in this study, however, had participants more broadly consider “any physical activity or exercise,” and it thus reflects total aerobic PA. Indeed, the findings of this study are in agreement with a study by Fan et al, in which the authors examined urban‐rural differences in PA using accelerometer and survey measures . In their analysis of accelerometer data, these researchers found no evidence for differences between urban and rural residents when using a low‐intensity cut‐off point to measure total aerobic PA.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The items used to measure aerobic PA in this study, however, had participants more broadly consider “any physical activity or exercise,” and it thus reflects total aerobic PA. Indeed, the findings of this study are in agreement with a study by Fan et al, in which the authors examined urban‐rural differences in PA using accelerometer and survey measures . In their analysis of accelerometer data, these researchers found no evidence for differences between urban and rural residents when using a low‐intensity cut‐off point to measure total aerobic PA.…”
Section: Discussionsupporting
confidence: 91%
“…21,22 Using accelerometer data of a nationally representative sample, Fan and associates found no difference between urban and rural residents' total aerobic PA levels; these authors did note that PA patterns differed such that rural residents engaged in less vigorousintensity PA, and they suggested that urban-rural health disparities may be attributable in part to this difference, or, alternatively, due to differences in other PA-related behaviors. 23 Limited literature has investigated differences in the other PA-related behaviors corresponding to national guidelines. One study conducted by Trivedi and colleagues found US rural residents to be slightly more likely to engage in 4 hours or more of leisure screen-time sedentary behavior (this is a subset of total sedentary behavior that may be particularly health-compromising).…”
mentioning
confidence: 99%
“…In addition, educational attainment is also associated with more awareness of the health benefits of AC and a stronger concern about environmental problems resulting from motorized transportation, which may facilitate the adoption of AC (Dietz et al, 1998). Past studies have found college graduates engage in more leisure time PA than individuals with lower levels of education (Cerin et al, 2009, Fan et al, 2014b, Fan et al, 2014c). Apparently, this association extends to the transportation domain of PA as well.…”
Section: Discussionmentioning
confidence: 94%
“…Unless there is evidence of different behavior in food and beverage intakes or different metabolism, one may question the reliability of PI (a subjective assessment loosely defined) in comparison to OB (a rather more objective measure based on BMI) (Wang et al 2013: 10–11). Also see Fan, Wen and Kowaleski-Jones (2014) for the difference in subjective and objective PI measures. We will keep this in mind, and hereafter focus more on the MLM results on obesity.…”
Section: Resultsmentioning
confidence: 99%